A sharp-switching device with free surface and buried gates based on band modulation and feedback mechanisms. (February 2016) - Solaro, Y.; Fonteneau, P.; Legrand, C.A.; Fenouillet-Beranger, C.; Ferrari, P.; Cristoloveanu, S.
Graphical abstract: Highlights: A sharp switching device without front gates fabricated with FDSOI. Output and transfer characteristics are very abrupt. The device features high breakdown voltage, low leakage and high ON current. The free surface enables improved ESD protection, memory and sensing applications. Abstract: We propose and demonstrate experimentally a band-modulation device with extremely sharp switching capability. The Z 3 -FET (Zero gate, Zero swing and Zero impact ionization) has no top gate, is processed with FDSOI CMOS technology, and makes use of two adjacent buried ground planes acting as back gates. The buried gates emulate respectively N + and P + regions in the undoped body, forming a virtual thyristor-like NPNP structure with feedback operation. Vertical output I A – V A and transfer I A – V G characteristics over more than 8 decades of current are measured with relatively low gate and drain bias (<3 V).